2020
DOI: 10.5339/qmj.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multi-Antibiotic Resistant Escherichia coli and Klebsiella species obtained from a Tertiary Medical Institution in Oyo State, Nigeria

Abstract: Background: The development of multi-antibiotic resistant bacteria, especially Gram-negative bacteria which are the major cause of hospital-acquired infections worldwide, had been increasing. Escherichia coli and Klebsiella sp. had become more resistant to different classes of antibiotics, and the treatment of infections caused by these bacteria had developed into a challenge in both developed and developing countries. This study had determined the multi-antibiotic resistance (MAR) patterns of Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 11 publications
5
34
2
2
Order By: Relevance
“…It represented 14% of isolated bacteria, and most of the isolates were MDR and exhibited ESBL and carbapenemase activities [ 14 ]. Examination of 48 K. pneumoniae strains isolated from Medical Institution in Oyo State, Nigeria, showed resistance in 88% of isolates to streptomycin and in 92% to cloxacillin, oxacillin, and colistin [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…It represented 14% of isolated bacteria, and most of the isolates were MDR and exhibited ESBL and carbapenemase activities [ 14 ]. Examination of 48 K. pneumoniae strains isolated from Medical Institution in Oyo State, Nigeria, showed resistance in 88% of isolates to streptomycin and in 92% to cloxacillin, oxacillin, and colistin [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…were resistant to ampicillin, amoxicillin, and cefuroxime but susceptible to gentamicin, ciprofloxacin, and amikacin. 32 Ayandele et al 33 also reported resistances of 87.5%, 68.75%, and 58.38% for streptomycin, gentamycin, and amikacin, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple antibiotic resistance index (MAR) is an effective method used in tracking sources of antibiotic resistant bacteria (Ayandele et al, 2020). Multiple antibiotic resistance (MAR) indices were calculated as a/(bxc) whereby a represented the aggregate of all antibiotic resistance scores of all the bacteria, b represented the total number of antibiotics used, and c was the number of the isolates.…”
Section: Antibiotic Susceptibility Testing (Ast) Of the Pathogenic Ba...mentioning
confidence: 99%